The Software Industry Economic Principles, Strategies, Perspectives - Buxmann, Peter; Diefenbach, Heiner; Hess, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Whether ERP software, office applications, open-source products or online games: In terms of its economic characteristics, software differs fundamentally from industrial goods or services. Based on the economic principles and rules of the software industry, the book reveals strategies and business models to software vendors that comprise cooperation, distribution, pricing and production and industrialization strategies, as well as software as a service and platform concepts. Further aspects including the outsourcing behavior of software vendors and users; providing business software as open source software; selecting software; and the value chains in the software industry are also addressed. Based on a number of expert meetings, it contains numerous case studies and new empirical findings. Target audience of the book are professionals and executives from the software, consulting and IT branches as well as students and scholars of business administration, computer science, business and industrial engineering.
A. Background: How the software industry works -- Economic principles at work in the software industry -- Software vendor strategies -- B. Specific Issues: Outsourcing and offshoring of software development -- Platform concepts -- Software as a Service. 7. Open source software.
Keywords: Economics; Software engineering; Industrial management; Management information systems; Economics/Management Science; Management/Business for Professionals; Business Information Systems; Innovation/Technology Management; e-Commerce/e-business.; Software Engineering/Programming and Operating Systems